Program Kemitraan Masyarakat (PK PERANGKAT ALAT PENGHEMAT ENERGI LISTRIK BERBASIS RASPBERRY MENGGUNAKAN SMARTPHONE: Sistem Kendali Perangkat Listrik - Yunus Tjandi; Zulhajji; Paloboran, Marthen; Mardiana; Vitalocca, Dyah (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
Improper utilization of electricity due to control that is not in accordance with PUIL standards, will cause great losses to consumers of electricity users. The objectives to be achieved in this PKM are: (1) to increase the knowledge of students and teachers of SMK Darussalam Maros (Partners) in making Raspberry-based electrical energy saving device software using a smartphone, which functions to control the use of electrical energy in a house / office, (2) to improve Partner skills in making and utilizing Raspberry-based electrical energy saving devices using smartphones, according to the software that has been made, (3) to improve Partner skills in making interfaces and applications for Raspberry-based electrical energy saving devices using smartphones. The methods used in this Workshop training are lecture, discussion, question and answer and demonstration methods. The results of this PKM are (1) Partners' knowledge in making Raspberry-based electrical energy saving device software is more improved, (2) Partners' skills increase in terms of making and utilizing Raspberry-based electrical energy saving devices, (3) Partners' skills are more improved in making interfaces and applications for electrical energy saving devices, so that these devices can be controlled through smartphones, both from close range, and from a distance.